Measuring Multiple Demographic Rates in Two Populations of Northern Bobwhite - Alexander L Jackson; D. Clay Sisson; Justin A. Rectenwald (National Quail Symposium Proceedings, 2022)
Demographic rates of northern bobwhite (Colinus virginianus; hereafter, bobwhite) may vary spatially and temporally, and understanding the significance of these individual rates to population performance is critically important to bobwhite management. We present descriptive evidence from 2 populations that were simultaneously monitored from 2015–2020 that suggests different demographic rates can be more important to population performance than other demographic rates within the same region. Our objective was to understand the relative importance of various demographic rates to population performance in separate and seemingly stable populations. We monitored bobwhite seasonal survival and reproductive demographics on 2,475 bobwhites via radio-telemetry and estimated fall density using fall covey counts. Both sites maintained high densities (i.e., ≥3.45 birds/hectare) and remained relatively stable throughout the study period. On one site in the Red Hills region near Monticello, Florida, USA, bobwhite experienced comparatively low seasonal survival, but higher reproduction, including more frequent multiple-brood production. One hundred and twenty-nine kilometers away on a study site near Albany, Georgia, USA, bobwhite demonstrated consistently higher survival and lower reproductive output, including less multiple-brooding compared to the Red Hills population. This suggests, at a minimum, that compensatory or density-dependent reproduction may be occurring in these populations and regional population dynamics can vary locally even among stable populations.
Keywords: Colinus virginianus; density-dependence; Florida; Georgia; multiple-brooding; northern bobwhite; productivity; survival